Conference report: Future Forces Forum Prague, world medical congress (CEBIRAM) 2018 - Quinn, John; Bencko, Vladimír; Osvald, Vratislav; Májovský, Peter; Král, Petr; Bubeník, Zoltán; Fazekas, Laszlo (Vojenské zdravotnické listy, 2019)
The Future Forces Forum in Prague occurs biennially and offers a premier venue to exchange best practices, ideas, academic and technical debate with key military decision makers on the future of military medicine. In the over 13 events in modern times, all sectors of military and defense forces have shared experiences, strategies of deterrence, common defense structures and modalities to mitigate human suffering and reduce the morbidity and mortality associated with conflict, war and disaster. Czech Republic Ministry of Defense Brigadier General Bubenik has taken the lead with this event to drive future innovation and all things battlefield medicine, to include chemical, biological, radiological and nuclear threats, with overall emphasis on emerging global health security threats. Under his tutelage, Brig. Gen. Bubenik has ushered in a marque venue for such debate at the Future Forces Forum, Prague 2018 (FFF 2018). The expert event took place from October 17th to the 19th, 2018 in Prague. This short conference report should serve as a synopsis of the key takeaways, in addition to highlighting some core conclusions to support all medical operations across NATO and at the civilian-military interface.
Keywords: Congresses as Topic; kongresy jako téma; Military Medicine; vojenské lékařství; lidé; Humans